CSF biomarkers for the differential diagnosis of Alzheimer's disease: A large‐scale international multicenter study. Issue 11 (23rd March 2015) - Ewers, Michael; Mattsson, Niklas; Minthon, Lennart; Molinuevo, José L.; Antonell, Anna; Popp, Julius; Jessen, Frank; Herukka, Sanna‐Kaisa; Soininen, Hilka; Maetzler, Walter; Leyhe, Thomas; Bürger, Katharina; et al.
Abstract: Introduction: The aim of this study was to test the diagnostic value of cerebrospinal fluid (CSF) beta‐amyloid (Aβ1–42 ), phosphorylated tau, and total tau (tau) to discriminate Alzheimer's disease (AD) dementia from other forms of dementia. Methods: A total of 675 CSF samples collected at eight memory clinics were obtained from healthy controls, AD dementia, subjective memory impairment, mild cognitive impairment, vascular dementia, Lewy body dementia (LBD), fronto‐temporal dementia (FTD), depression, or other neurological diseases. Results: CSF Aβ1–42 showed the best diagnostic accuracy among the CSF biomarkers. At a sensitivity of 85%, the specificity to differentiate AD dementia against other diagnoses ranged from 42% (for LBD, 95% confidence interval or CI = 32–62) to 77% (for FTD, 95% CI = 62–90). Discussion: CSF Aβ1–42 discriminates AD dementia from FTD, but shows significant overlap with other non‐AD forms of dementia, possibly reflecting the underlying mixed pathologies.